Hemodynamic Analysis of Postoperative Rupture of Unruptured Intracranial Aneurysms after Placement of Flow-Diverting Stents: A Matched Case-Control Study - Li, W.; Tian, Z.; Zhu, W.; Zhang, Y.S.; Wang, K.; Zhang, Y.; Wang, Y.; Yang, X.; Liu, J. (American journal of neuroradiology : AJNR, 2019)
Postoperative rupture of intracranial aneurysm has been reported as a fatal complication after flow-diverter placement. We assessed several hemodynamic variables to explore risk factors in the postoperative rupture process. We enrolled 10 patients with intracranial aneurysms, treated with flow diverters between September 2014 and December 2018, who experienced postoperative aneurysm rupture (postoperative aneurysm rupture group). We matched these subjects 1:2 with 20 patients with postoperative unruptured (postoperative unruptured group) intracranial aneurysms based on clinical and morphologic factors. Using computational fluid dynamics, we assessed hemodynamic changes pre- and posttreatment between the 2 groups on a number of qualitative and quantitative parameters. In the postoperative aneurysm rupture group, the proportion of patients with aneurysms with an unstable flow pattern increased to 60.0% after treatment, while the proportion in the postoperative unruptured group decreased to 20.0%, a significant difference between the 2 groups ( = .028). Energy loss in the postoperative unruptured group decreased after treatment but increased in the postoperative aneurysm rupture group. The reduction ratio of energy loss showed a significant difference between the 2 groups (22.73% ± 53.59% for postoperative unruptured versus -158.81% ± 183.95% for postoperative aneurysm rupture, = .02). Other parameters and changes of pre- and posttreatment hemodynamic parameters showed no significant difference between 2 groups. Compared with pretreatment, unstable flow pattern and higher energy loss after Pipeline Embolization Device placement for intracranial aneurysm may be the important hemodynamic risk factors related to delayed aneurysm rupture.